Tick-Borne Encephalitis: A Differential Pattern of Intrathecal Humoral Immune Response and Inflammatory Cell Composition Compared with Other Viral CNS Infections - Makbule Senel; Daniel Rapp; Benjamin Mayer; Sarah Jesse; Sigurd D. Süssmuth; Markus Otto; Jan Lewerenz; Hayrettin Tumani (Cells, 2020)
To investigate whether and how cerebrospinal fluid (CSF) findings can contribute to distinguish tick-borne encephalitis (TBE) from herpes simplex virus (HSV) and varicella zoster virus (VZV) induced central nervous system (CNS) infections (HSV-I, VZV-I). Chart review and identification of TBE, HSV- I, and VZV-I was carried out, fulfilling the following criteria: (1) clinical signs of encephalitis and/or meningitis, (2) complete CSF analysis and confirmed viral etiology by either PCR or antibody testing in CSF, (3) hospitalized patients, and (4) available brain magnetic resonance imaging (MRI). Fifty-nine patients with 118 CSF/serum pairs were included. These comprised 21 with TBE (35 CSF/serum pairs), 20 (40 CSF/serum pairs) with HSV-I, and 18 (43 CSF/serum pairs) with VZV-I. In contrast to HSV-I and VZV-I, CSF cell differentiation in TBE showed more often an increased (>20%) proportion of granulocytes (p < 0.01) and a more frequent quantitative intrathecal IgM synthesis (p = 0.001 and p < 0.01, respectively), while the second was even more pronounced when follow-up CSF analyses were included (p < 0.001). CSF findings help to distinguish TBE from other viral infections. In cases with CSF pleocytosis and a positive history for a stay in or near an endemic area, TBE antibodies in CSF and serum should be determined, especially if granulocytes in CSF cell differentiation and/or an intrathecal IgM synthesis is present.